Trends in Cytomorphological Study of Thyroid lesions: A two year prospective study in the malwa region of central India - Preeti Rihal Chakrabarti; Poonam Mishra; Chakrabarti Suvadip; Rashmi Patidar; Akansha Jain; Priyanka Gupta (International Journal of Medical Research and Review, 2016)
Background: Thyroid lesions are commonly encountered in daily clinical practice. However, excision of thyroid lesions is associated with risk. Hence an effective preliminary test is needed to avoid unnecessary surgery. An assessment of thyroid lesion by FNAC has proved to provide early diagnosis and hence helps in avoiding invasive surgery.Aims and Objectives: The purpose of present study was to study various cytomorphological features of thyroid lesions in the tertiary teaching hospital of Malwa region with respect to age, sex and to categorize them into neoplastic and non-neoplastic lesions.Materials and methods: FNAC was performed on patients who presented with thyroid swelling in department of pathology of Sri Aurobindo Medical College and PG Institute, from 1st January 2014 to 31st December 2015.Results: Out of 186 patients in our study group 161(86.56%) were benign, 23(12.37%) were malignant and 2 were inconclusive. Benign follicular lesion 108 (67%) was commonest under non-neoplastic category and follicular neoplasm 19 (82.6%) under neoplastic category. Male to female ratio was 1:4.Conclusion: FNAC plays an important role in thyroid lesions as it is safe, cost effective and also helps in selections of patients for surgery, thus minimizing risk associated with surgery.